Synthesis of akaganeite in the presence of sulfate: Implications for akaganeite formation in Yellowknife Bay, Gale Crater, Mars. (1st September 2016) - Peretyazhko, T.S.; Fox, A.; Sutter, B.; Niles, P.B.; Adams, M.; Morris, R.V.; Ming, D.W.
Abstract: Akaganeite, a Cl-bearing Fe(III) (hydr)oxide, has been recently discovered in Yellowknife Bay in Gale crater on Mars by the Mars Science Laboratory (MSL) Curiosity Rover. Akaganeite was associated with sulfate and sulfide minerals at Yellowknife Bay indicating that sulfate ions could be present in solution during akaganeite formation. The mechanism and conditions of akaganeite formation in the Yellowknife Bay mudstone are unknown. We investigated formation of akaganeite through hydrolysis of ferric chloride solution in the presence of 0, 0.01, 0.05, 0.1 and 0.2 M sulfate and at initial pH of 1.5, 2 and 4 at 90 °C. Mineralogy of the precipitated Fe(III) phases was characterized by X-ray diffraction and infrared spectroscopy. The precipitates were also acid digested to determine total sulfate and chloride contents. Akaganeite and natrojarosite formed at initial solution pH of 1.5; akaganeite, goethite and natrojarosite precipitated in initial pH 2 solutions and goethite, hematite and 2-line ferrihydrite precipitated at initial solution pH of 4. Sulfate addition did not inhibit akaganeite formation. Increasing initial solution sulfate concentrations resulted in increasing sulfate to chloride ratio in the precipitated akaganeite. Infrared spectroscopy revealed akaganeite bands at ∼2 μm (H2 O combination band) and at ∼2.46 μm (OH combination band). The H2 O combination band position linearly correlated with total chloride content in akaganeite. Overall, laboratory studies demonstrated formation of akaganeite at initial sulfate concentration ⩽0.2 M (sulfate to chloride molar ratio ⩽0.3) and pH ⩽ 2, implying that those conditions might prevail (perhaps as micro-environments) during akaganeite formation in Yellowknife Bay mudstone. The occurrence of Fe(II) sulfides (pyrite and pyrrhotite) in Yellowknife Bay mudstone is a potential acidity source. Dissolution of sulfide minerals might occur under localized oxidizing water-limiting Cl-rich conditions creating favorable environments for akaganeite formation.